Embryonic Stem Cells and Infertility - Lorzadeh, Nahid; Kazemirad, Nastaran (American Journal of Perinatology, 2018)
Embryonic stem cells (ESCs) have the ability to differentiate into several cell lineages and self-renew. Through a spontaneous process, ESCs can differentiate into germ cells of various stages, partly due to their self-renewal ability and their microenvironment culture. Human and mouse ESC differentiation into putative primordial germ cells (PGCs) has been demonstrated by several studies; in fact, derivation of functional mouse male gametes has also been reported. However, the exact underlying mechanisms are yet to be understood properly, and as such clinical applications of ESC-derived PGC remains controversial. Nonetheless, this technique can still serve as a potential treatment option for infertility. This review centers on the available reports on the possible application of ESC for infertility treatment.
Keywords: embryonic stem cell; infertility; primordial germ cells; pluripotency; embryoid bodies